Comparison Of Peppermint And Ginger Essential Oil On The Reduction Of Back Pain Intensity In Pregnant Women In The Third Trimester In The Working Area Of Munjul Jaya Community Health Center, Purwakarta Regency, 2025 - Maulida Lathifah; Qurotul Aini (International Journal of Health and Pharmaceutical (IJHP), 2026)
Back pain is one of the discomforts most frequently experienced by pregnant women, especially in the third trimester. In Indonesia, the prevalence of back pain among third-trimester pregnant women is reported to be around 70%. Peppermint and ginger contain compounds that can help reduce this problem. This study used a quasi-experimental design with a two group pretest posttest design. The first group was given peppermint essential oil and the second group was given ginger essential oil. A total of 50 respondents were selected using purposive sampling and given the intervention 4 times over a period of 2 weeks. The Wilcoxon test results showed p-value of 0.000 in both groups, so both peppermint essential oil and ginger essential oil had a significant effect on reducing the intensity of back pain in third-trimester pregnant women. The Mann-Whitney test obtained a p-value of 0.149, indicating no difference between the peppermint essential oil and ginger groups in reducing pain intensity. Thus, peppermint and ginger essential oils are beneficial as non-pharmacological treatments